1984
DOI: 10.1038/307637a0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental chimaeras—removal of reproductive barrier between sheep and goat

Abstract: Following reciprocal embryo transfer between sheep and goats, the embryo of the foreign species is able to induce early pregnancy but the embryos do not survive beyond the first weeks of gestation. Similar results have been obtained from hybridization experiments on sheep and goats. While the causes for early embryonic death of hybrid eggs from donor sheep are unknown, the reciprocal event has been associated with immunological implications. As a means of overcoming the reproductive barrier between sheep and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(24 citation statements)
references
References 7 publications
2
22
0
Order By: Relevance
“…Rossant et al (1983) contended that the trophoblast was the critical factor in embryo survival as, in the mouse system, the donor inner cell mass could survive indefinitely if injected into maternal host blastocysts. This was also true in the sheep-goat cross, as mixing donor with maternal host blastocysts, or surrounding them with a host zona pellucida, so that the chorionic epithelium of the placenta developed from cells of the maternal host, resulted in the birth of sheep-goat hybrids (Fehilly et al, 1984;Meinecke-Tillmann and Meinecke, 1984). This finding implies that the surface characteristics of the trophoblast are of significance in establishing and maintaining a viable pregnancy, whether due to an immune response or other factors that contribute to the formation of a stable interface or intercellular adhesion, which in camels is a prolonged and complex process (Abd-Elnaeim et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rossant et al (1983) contended that the trophoblast was the critical factor in embryo survival as, in the mouse system, the donor inner cell mass could survive indefinitely if injected into maternal host blastocysts. This was also true in the sheep-goat cross, as mixing donor with maternal host blastocysts, or surrounding them with a host zona pellucida, so that the chorionic epithelium of the placenta developed from cells of the maternal host, resulted in the birth of sheep-goat hybrids (Fehilly et al, 1984;Meinecke-Tillmann and Meinecke, 1984). This finding implies that the surface characteristics of the trophoblast are of significance in establishing and maintaining a viable pregnancy, whether due to an immune response or other factors that contribute to the formation of a stable interface or intercellular adhesion, which in camels is a prolonged and complex process (Abd-Elnaeim et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…There have been many attempts to produce hybrids between unrelated species; other than the camel-llama cross there have also been attempts to cross laboratory and wild mice species (Rossant et al, 1982(Rossant et al, ,1983, mice and bank voles (Mystkowska, 1975), and sheep and goats (Fehilly et al, 1984;Meinecke-Tillmann and Meinecke, 1984). In most cases, the embryos do not survive to term.…”
Section: Discussionmentioning
confidence: 99%
“…For example, goat x sheep placentae showed abnormal contact at the feto-maternal junction [6]. Later experiments to produce chimaeras between sheep and goat [7][8] or between two mouse species (Mus caroli and Mus musculus), demonstrated that if the implanting embryo were manipulated to produce a chimaeric blastocyst in which the outer trophectoderm cells came from the same species as the recipient, the chances of survival were greatly increased [9][10][11]. This manoeuvre used compatible trophoblast to protect a foreign fetus from an adverse maternal response.…”
Section: Introductionmentioning
confidence: 99%
“…While the frequent failure of xenogeneic pregnancies may be caused by immunological rejection of the conceptus by the mother, such a mechanism for pregnancy loss, if occurring, does so despite the inhibitory actions of progesterone on uterine immune function. Indeed, the birth of chimeric individuals [4]as well as hybrid animals such as mules and hinnies [5]argues for an effective mechanism for inhibiting xenogeneic immune responses in utero. Progesterone is likely to represent an important component of this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the conceptus, which is a foreign allograft, routinely survives in the uterus. In some cases, pregnancies as antigenic as those representing xenografts can be successfully maintained to term [4, 5]. The major evidence that progesterone plays an important role in uterine acceptance of foreign tissue during pregnancy is the wide range of immunosuppressive actions attributed to this hormone.…”
Section: Introductionmentioning
confidence: 99%